Efektivitas Pemberian Terapi Relaksasi Otot Progresif Terhadap Penurunan Tingkat Stres Pada Perawat : Systematic Review - Mandasari, Linda; Daulima, Novy Helena Catharina; Mustikasari, Mustikasari; Putri, Yossie Susanti Eka (Jurnal Ners, 2025)
Nurses are at the forefront of health services so they can influence the physical and psychological condition of nurses. Psychological disorders that can occur include work stress on nurses which must be studied and solutions found so that nurses' performance remains good and of high quality. To overcome work stress conditions in nurses, there are various solutions that can be done, one of which is progressive muscle relaxation. Progressive muscle relaxation therapy can have an effect on reducing stress and anxiety levels in nurses. Literature search using databases namely ProQuest, Sciencedirect and Clinicalkey Nursing within the last 10 years. There are 3 articles that use a Randomized Control Trial. Providing progressive muscle relaxation therapy can be effective in reducing stress levels in nurses.